Pressure and Flow Control System to Prevent Drinking Water Pipe Leaks - Putri Yeni Aisyah; Akhmad Ibnu Hija; Ega Prawira Hadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The distribution of water through pipes experienced an average water loss of 35%. This is caused by a lack of pipe management, measurement tool management, and pressure management. In this study, a drinking water company miniplant was made using PVC pipe as a simulation to show the action of the solenoid valve as a pressure controller and water flow rate against leakage. This study monitors pressure differences and flow rates. Global valve acts as an actuator to control flow pressure while ball valve acts as an actuator to control flow rate. The results of the validation of the pressure sensor, on average the four sensors produce an accuracy of 99.587% and an inaccuracy of 0.413%. The results of the flow sensor validation, the average of the four sensors produces an accuracy of 97.558% and an inaccuracy of 2.442%. The results of system testing on the solenoid valve pressure control, work according to the set point in controlling pressure. The results of system testing on the solenoid valve pipe leakage control, work according to the set point in controlling pipe leakage but the ratio is high. The ratio is too high because the flow after the solenoid valve is getting slower, but the flow before the solenoid valve is still moving to fill the empty space in the pipe until there is no water flow.